Anamorphic phase of Glomerella cingulate in cowpea in Rio de Janeiro state - Nogueira, Maria do Socorro Rocha; Brioso, Paulo Sergio Torres (Comunicata Scientiae, 2015)
The social and economic importance of cowpea (Vigna unguiculata) is increasing in the State of Rio de Janeiro (RJ), and in consequence, there has been an emergence of some pathogens that can influence the yield. The aim of this study was to identify the etiologic agent associated with necrosis of leaf abaxial rib cowpea grown in the municipality of Seropédica (RJ). Anamorph (Colletotrichum lindemuthianum) of Glomerella cingulata was identified in plants of cowpea and in seeds the incidence being around 2%. This is the first report of this fungus on cowpea in the State of Rio de Janeiro.